2015
DOI: 10.1002/pon.3833
|View full text |Cite
|
Sign up to set email alerts
|

The role of emotions in time to presentation for symptoms suggestive of cancer: a systematic literature review of quantitative studies

Abstract: Background: Emotions may be important in patients' decisions to seek medical help for symptoms suggestive of cancer.Objectives: The aim of this systematic literature review was to examine quantitative literature on the influence of emotion on patients' help-seeking for symptoms suggestive of cancer. The objectives were to identify the following: (a) which types of emotions influence help-seeking behaviour, (b) whether these form a barrier or trigger for seeking medical help and (c) how the role of emotions var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 56 publications
5
49
0
Order By: Relevance
“…Another item mentioned feeling uncomfortable thinking about cancer, and that was associated with lower attendance; the worry item was interpreted as more ‘cognitive’ and the ‘uncomfortable’ item as more visceral. The present study results fit somewhat with this model and may also help explain previous mixed findings in relation to the role of emotions in time to presentation . Worry – even frequent worry – motivated help‐seeking partly as a means of alleviating it.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Another item mentioned feeling uncomfortable thinking about cancer, and that was associated with lower attendance; the worry item was interpreted as more ‘cognitive’ and the ‘uncomfortable’ item as more visceral. The present study results fit somewhat with this model and may also help explain previous mixed findings in relation to the role of emotions in time to presentation . Worry – even frequent worry – motivated help‐seeking partly as a means of alleviating it.…”
Section: Discussionsupporting
confidence: 86%
“…Another study, focusing specifically on fear intensity concluded that higher levels of fear facilitated rather than hindered help‐seeking . Finally, a recent systematic review of studies with patients also highlighted the mixed impact of emotions on time to presentation, concluding that more emotion‐focused research was needed in order to unravel its complexity .…”
Section: Introductionmentioning
confidence: 99%
“…One potential explanation is the mixed role of emotion in help-seeking [31], where cancer worry can act both as a barrier and facilitator to contacting a health care professional [32]. …”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of 102 studies from 26 countries showed that people fear a cancer diagnosis because cancer is considered a vicious, unpredictable enemy that attacks unannounced, and often leads to death of the victims . While fear about getting cancer may prompt screening for cancers, fear about cancer treatment may lead to delayed help‐seeking to avoid being diagnosed with a cancer . Cancer treatments have been feared because of their side effects including psychosocial and bodily changes .…”
Section: Introductionmentioning
confidence: 99%